Colonies of Gyrosigma eximium: a new phenomenon in Arctic tidal flats - Józef Wiktor; Agnieszka Tatarek; Jan M. Węsławski; Lech Kotwicki; Michel Poulin (Oceanologia)
For the first time at Svalbard, a colonial form of the tube-dwelling diatom Gyrosigma eximium was found in summer 2010 in the tidal flats on Spitsbergen at 78°N. The colonies take the form of conical, green structures that are 1–2 cm high and are associated with other diatom taxa and cyanobacteria (Oscillatoriaceae). The diatom colonies were associated with rich meiofauna and apparently act as cohesive factors for the fine sediment. In the Arctic tidal flats, this represents the first observation of long-term sediment stabilization and biological enrichment. Since this first observation, this species has apparently colonized broader areas in Advenentelva's tidal flat.